Timing and route of contamination of hospitalized patient rooms with healthcare-associated pathogens. (12th September 2021) - Redmond, Sarah N.; Pearlmutter, Basya S.; Ng-Wong, Yilen K.; Alhmidi, Heba; Cadnum, Jennifer L.; Silva, Sandra Y.; Wilson, Brigid M.; Donskey, Curtis J.
Abstract: Objective: To investigate the timing and routes of contamination of the rooms of patients newly admitted to the hospital. Design: Observational cohort study and simulations of pathogen transfer. Setting: A Veterans' Affairs hospital. Participants: Patients newly admitted to the hospital with no known carriage of healthcare-associated pathogens. Methods: Interactions between the participants and personnel or portable equipment were observed, and cultures of high-touch surfaces, floors, bedding, and patients' socks and skin were collected for up to 4 days. Cultures were processed for Clostridioides difﬁcile, methicillin-resistant Staphylococcus aureus (MRSA), and vancomycin-resistant enterococci (VRE). Simulations were conducted with bacteriophage MS2 to assess plausibility of transfer from contaminated floors to high-touch surfaces and to assess the effectiveness of wearing slippers in reducing transfer. Results: Environmental cultures became positive for at least 1 pathogen in 10 (59%) of the 17 rooms, with cultures positive for MRSA, C. difficile, and VRE in the rooms of 10 (59%), 2 (12%), and 2 (12%) participants, respectively. For all 14 instances of pathogen detection, the initial site of recovery was the floor followed in a subset of patients by detection on sock bottoms, bedding, and high-touch surfaces. In simulations, wearing slippers over hospital socks dramatically reduced transfer of bacteriophage MS2 from the floor to hands and to high-touch surfaces. Conclusions: Floors may be an underappreciated source of pathogen dissemination in healthcare facilities. Simple interventions such as having patients wear slippers could potentially reduce the risk for transfer of pathogens from floors to hands and high-touch surfaces.